Assisting Teachers in Integrating Technology to Improve Learning Quality in Remote Schools - Liliana, Mâţă (Edujavare Publishing, 2025)
This community service aimed to empower teachers in remote schools to integrate technology effectively to improve learning quality. The initiative was driven by the challenge of limited digital literacy and infrastructure among teachers in rural areas, which often leads to unequal learning opportunities compared to urban schools. Using the Participatory Action Research (PAR) approach, the program involved teachers as active collaborators in identifying needs, planning actions, implementing digital-based learning, and reflecting on outcomes. Data were collected through observation, interviews, focus group discussions, and pre- and post-tests, and analyzed using qualitative analysis and correlation testing. The results showed significant improvement in teachers’ digital competence, pedagogical creativity, and students’ engagement, with a strong positive correlation (r = 0.81) between digital literacy and teaching quality. The program concluded that participatory mentoring fosters teacher empowerment, pedagogical transformation, and sustainability of technology use in remote education. The contribution of this project lies in its model of contextual, participatory, and sustainable digital empowerment for rural teachers.